“Modos y maneras del uso de medicamentos en las familias del cercado del distrito de Ayacucho” - Arones Jara, Marco Rolando (2019)
ABSTRACT Objective: Describe and understand the modes and ways in the use of medicines from the perspective of the families of the fencing of the district of Ayacucho-Peru. Methods: Qualitative descriptive-exploratory study. The sample consisted of 15 families defined by saturation who participated in a semi-structured interview, during 2017. Speech analysis was used for category identification and grounded theory for data analysis. Results: Three themes: The family, the disease and the use of medications, the health system as a determinant of the use of medications in families and alternative and/or complementary therapy. Final Considerations: In families, mothers play a very important role in the health and treatment of the disease, so they decide on the modes and ways of using medications. The modes are referred to the perception of the severity or severity of the disease, the knowledge and experiences about the disease and the use of medications, the perception of the importance and efficacy of medications; Perceptions of fear and fear of medication. These modes determine the ways of using medications in families, which are characterized by self-medication as an expression of family care, the agency of self-care of dependents and self-care. The perception of the severity of the disease, the inaccessibility and dissatisfaction, determine the ways of using medicines in pharmaceutical and health establishments; as well as, the sources of information and the use of home remedies condition the ways of using medications in families.